Application of immunoPET imaging to enhance head and neck squamous cell carcinoma clinical management - Almutairi, Waleed M.; Zheng, Qi-Huang; Langer, Mark; Oderinde, Oluwaseyi M. (Frontiers in Oncology, 2025)
BackgroundHead and neck squamous cell carcinoma (HNSCC) remains a significant clinical challenge due to high recurrence, therapy resistance, and limited biomarkers. The tumor microenvironment (TME) plays a critical role in determining treatment outcomes. Immuno-positron emission tomography (immunoPET), which combines the specificity of monoclonal antibodies (mAbs) with the sensitivity of PET, offers non-invasive visualization of immune activity and guidance for treatment. This review summarizes the applications of immunoPET in HNSCC.MethodsFollowed PRISMA 2020 guidelines, 1686 records were identified through searches of PubMed, Embase, Scopus, and Web of Science (January 1, 1999, to May 11, 2025). Only 11 studies on immunoPET in HNSCC met the inclusion criteria and were evaluated for imaging targets, radiotracers, injection approaches, and preclinical or clinical outcomes. Methodological quality was assessed using the Quality Assessment of Diagnostic Accuracy Studies (QUADAS-2) and the Systematic Review Center for Laboratory Animal Experimentation (SYRCLE) tools.ResultsSix preclinical and five clinical studies investigated five immune-related targets: programmed death-ligand 1 (PD-L1), epidermal growth factor receptor (EGFR), tenascin-C, the extra domain B (ED-B) of fibronectin, and cluster of differentiation 44 variant 6 (CD44v6). PD-L1 imaging demonstrated safety and feasibility but lacked predictive accuracy. EGFR imaging showed high preclinical receptor-specific specificity, whereas clinical performance revealed cetuximab tumor accessibility, which was undetectable by FDG PET, with significant variability between patients. Tenascin-C imaging was localized to tumors but missed some lymph node metastases. ED-B imaging visualized tumor angiogenesis and reliably predicted therapeutic biodistribution, while CD44v6 emerged as the most consistently evaluated and promising for clinical translation.ConclusionImmunoPET holds promise for patient stratification and early response monitoring in HNSCC. Evidence remains limited, primarily due to small cohorts, heterogeneous protocols, narrow target diversity, and reliance on long-lived tracers. Future research should broaden the immune target, optimize imaging protocols, and develop short-lived tracers (e.g., 18F, 68Ga) for broader clinical integration.